Serum visfatin concentration and biochemistry parameter relationship of obese adolescents in Thailand. - Mahaweerawat, Udomsak; Somdee, Thidharat; Sungkamanee, Suvimol; Yangyuen, Suneerat (Asia-Pacific Journal of Science and Technology, 2017)
Visfatin is a recently discovered adipokine that is produced by the intra-abdominal adipose tissue which facilitates adipogenesis and has insulin-mimetic properties. The plasma levels of visfatin increase in parallel with obesity, but its role in adolescents remains largely unknown. This research aimed to determine serum visfatin concentration levels in Thai adolescents (15-18 years) and the relationship between visfatin concentration and biochemical parameters in obese adolescents. The research protocol and 77 consenting students who enrolled in this study were approved ethically by Mahasarakam research ethics committee. The mean serum visfatin level was 52.91 ng/ml in the obese adolescent while it was 23.80 ng/ml in the normal group. The data demonstrated that serum visfatin level was elevated in obesity, and positive correlations were observed between serum visfatin levels with body weight (p<0.001) and serum triglyceride (p<0.05) in obese adolescents. Even though the serum visfatin levels were slightly low in the normal group, there was still a statistically significant relationship with bicep skinfold thickness (p<0.05) and fasting blood sugar (p<0.05). In conclusion, these findings showed the relationship between visfatin levels and body weight and serum triglyceride in obese adolescents.